2012
DOI: 10.1021/ma3012976
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Capture of Self-Assembled Rosette Nanotubes

Abstract: Rosette nanotubes (RNTs) are self-assembled tubular architectures which have extensive chemical and physical tuning capabilities, owing to their ease of surface functionalization and flexible inner channel design. To marry these tunable features of the RNTs with the enhanced stability of a covalent polymer, here we demonstrate the covalent capture of the RNT supramolecular structure by polymerizing alkyldiamine functional groups expressed on their outer periphery in the presence of adipoyl chloride (nylon-6,6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…They created a heterobicyclic G C monomer containing the Watson–Crick DDA H‐bond array of guanine and the AAD array of cytosine (Figure a). Because of the asymmetry of its H‐bonding edges, the G C monomer undergoes self‐assembly in water as well as in polar solvents to form a six‐membered macrocycle maintained by 18 H‐bonds. The resulting hexameric rosette then self‐organizes hierarchically to produce tubular stacks (named rosette nanotubes, RNs) with tunable dimensions and properties (Figure b).…”
Section: Hydrogen‐bonded Macrocycles In Solutionmentioning
confidence: 99%
“…They created a heterobicyclic G C monomer containing the Watson–Crick DDA H‐bond array of guanine and the AAD array of cytosine (Figure a). Because of the asymmetry of its H‐bonding edges, the G C monomer undergoes self‐assembly in water as well as in polar solvents to form a six‐membered macrocycle maintained by 18 H‐bonds. The resulting hexameric rosette then self‐organizes hierarchically to produce tubular stacks (named rosette nanotubes, RNs) with tunable dimensions and properties (Figure b).…”
Section: Hydrogen‐bonded Macrocycles In Solutionmentioning
confidence: 99%
“…This task was complemented using a model of the rat homologous Kv1.1 channel, derived from the crystallographic structure of Kv1.2, 12 to perform molecular modelling of its interaction with the porphyrins. The porphyrins examined in this (10)(11)(12)(13)(14)(15)(16)(17)(18) study are shown in Scheme 1. Of particular interest was to determine the effects on Kv1 selectivity of porphyrin substituent chain length (10-13), amide linkage (14), primary amine groups (17,18) and multiple charged groups (15,16).…”
mentioning
confidence: 99%
“…The porphyrins examined in this (10)(11)(12)(13)(14)(15)(16)(17)(18) study are shown in Scheme 1. Of particular interest was to determine the effects on Kv1 selectivity of porphyrin substituent chain length (10-13), amide linkage (14), primary amine groups (17,18) and multiple charged groups (15,16). Four of the compounds purified were shown electrophysiologically to inhibit Kv1.1, 1.2 or both homo-tetrameric channels expressed in mammalian cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation